The Effectiveness of Positive Thinking Training on Improving Mental Health in Residents of the RT 15 Community, Pasir Putih Subdistrict, South Jambi District, Jambi City - FRANSISKA SITEPU; Anipah Anipah; Irwandi Irwandi; Erwinsyah Erwinsyah (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2026)
This research was motivated by the increasing mental health problems in society caused by social, economic, and psychological pressures in daily life. This condition highlights the importance of promotive and preventive efforts to improve community mental health through a positive psychology approach. The study aimed to determine the effectiveness of positive thinking training on improving mental health among residents of RT 15 Pasir Putih Subdistrict, South Jambi District, Jambi City. This research used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 60 respondents selected using total sampling technique. Data were collected using the Mental Health Continuum–Short Form (MHC-SF) questionnaire and analyzed using descriptive statistics and Pearson correlation tests with SPSS software. The results showed that before the training, the majority of respondents were in the moderate mental health category (83.3%), while after the training, the majority were in the high category (96.7%). The Pearson correlation test showed a correlation coefficient value of 0.723 with a significance value of 0.000 < 0.05, indicating a strong and significant relationship between positive thinking training and improved mental health. This study concludes that positive thinking training is effective in improving community mental health through increased optimism, positive emotional management, and the ability to cope with life pressures. This research is expected to serve as a reference for developing community-based mental health programs.